Deployment of STATCOM with Fuzzy Logic Control for Improving the Performance of Power System under Different Faults Conditions - Fawzy, Ibram Y.; Mossa, Mahmoud A.; Elsawy, Ahmed M.; Suwarno, Iswanto; Diab, Ahmed A. Zaki (Universitas Muhammadiyah Yogyakarta, 2024)
This paper purposes to demonstrate the effectiveness of fuzzy logic controller (FLC) over proportional integral (PI) controller for reducing the fault current and maintaining the voltage profile at different faults conditions using Static Synchronous Compensator (STATCOM) which is considered an effective FACTS (Flexible Alternating Current Transmission System) device. The study evaluates the performance of a power system equipped with STATCOM which is connected in shunt with bus B1 under various faults conditions, including single-phase and three-phase faults. The performance of the STATCOM is evaluated by using two different controllers: PI controllers and FLCs. A comparative analysis is done between the performances of the two different controllers using Matlab/Simulink software package. The results obtained conclude that the presented system gives better performance with STATCOM as compared to not using it under several faults conditions besides, the STATCOM gives better response with FLC as compared to PI controller. It is demonstrated that STATCOM with FLC can reduce the positive sequence fault current at bus B1 ‎to 96.49% of its value without ‎using STATCOM under line to ground fault and 98.17% under three line to ‎ground fault whereas STATCOM with PI controller can reduce it ‎to (99.57, 99.05%), respectively. Also, the bus voltage B1 is improved to 102.19% by using STATCOM with fuzzy controller under line to ground fault and 101.86% under three line to ‎ground fault whereas STATCOM with PI controller can improve it ‎to (100.21, 100.93%), respectively.